Community outreach nutrition education materials based on local nutrient-dense underutilized foods for low literate population using linear programming - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
2019: See document National Committee on food and nutrition security in Bénin where videos and Bioversity International are mentioned several times throughout the document. available at teamspace. 2018: Posters and dissemination workshops held at both community and district-level to build capacity on use of the tools were developed.